Medios audiovisuales en la conciencia ambiental de estudiantes de secundaria del Colegio Nacional Madre Teresa de Calcuta Loreto 2024 - Garcia Oliveira, Damaris Meily (2024)
This investigation was developed in the Center Educational Mother Teresa from Calcutta with students of the 4to of secondary with the purpose of determining the importance of the means visual audio in the teaching on the environment, the population was 80 students of the section " B " and the sample they conformed it 40 of them, the work was not experimental of methodology observational, tabulated evaluative of descriptive design the obtained data you ended up concluding: Relating that if in some subject the topic is played it has more than enough audiovisual means 6 they responded that yes and most (34) they not responded, 40 responded that if they would like to participate in a debate on environmental topics, in the same way all said that if they would like that means visual audio are used in the development of the classes, also the 40 of they show it they manifested that, if they would like to leave more followed to the field and they don't agree about the current environmental contamination 32 of them worry about it and they agree on wanting to have knowledge on more environmental topics through means visual audio, 35% is conscious that their attitudes affect to the environment, 85% considers necessary that the schools play more topics on the environment, 60% is conscious that it is necessary reutilizer some generated residuals and 100 apparent% to use the water appropriately.